Patotipos de Escherichia coli diarreiogênica em crianças quilombolas com e sem diarréia, do norte do Espírito Santo - Lozer, Diego Martins (2011)
Diarrhea remains an important public health problem for children of low socio-economic level families in developing countries, particularly in Brazil. Diarrheagenic Escherichia coli (DEC) strains are among the most important bacterial causes of childhood diarrhea. There are six pathotypes of DEC: enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), enteroinvasive E. coli (EIEC), shiga-toxin producing E. coli (STEC), enteroaggregative E. coli (EAEC) and diffuse adherent E. coli (DAEC). Detection of DEC has been facilitated by tissue culture assays as well as by DNA probes specific to each group of E. coli and used in hybridization assays. PCR primers have been also developed for all DEC types. The aim of this study was to investigate the presence of DEC strains, in children under 12 years of age living in Quilombolas Communities in São Mateus and Conceição da Barra-north of the Espirito Santo State. A total of 425 stool samples from children with diarrhea (n = 106) and without (n = 319) diarrhea were collected between August 2007 and December 2009. Stool samples were examined for the presence of E. coli, Salmonella spp and Shigella spp with MacConkey and Hektoen agar. All E. coli isolates were screened for the presence of DEC markers by monoplex and multiplex PCRs for detection of tEPEC (eaeA, bfpA), aEPEC (eaeA), EAEC (pCVD432), ETEC (elt and est), EIEC (ipaH), and STEC (stx1 and stx2). E. coli isolates were also tested for colony DNA hybridization with by using the eae, pAA and afaBC probes and by the HEp-2 adhesion assay to identify the LA, DA, and AA adherence patterns. E. coli and Shigella spp were isolated from 90% and 1.4%, respectively, and no Salmonella spp were isolated from any of the children. The most prevalent DEC was EAEC (43.9%), followed by DAEC (18.1%), aEPEC (13.1%), ETEC (2.3%), tEPEC (0.8%), EIEC (0.5%) and 0% EHEC. Of the 168 EAEC with AA, 40.5% were positive with the pCVD432 PCR and 25.6% reacted with the pAA probe. The afaBC probe detected 52.9% of the 69 DAEC isolates with DA. DAEC isolates with DA were detected significantly more often in children with diarrhea (23.6%) than in children without diarrhea (13.8%) (P = 0.022). In this study, isolation of two or more than two DEC types was common and associated with diarrhea (P = 0.0018)